The Role of Technology in Enhancing HR Compliance and Workforce Management: Implications for Organizational Agility and Employee Development - Andi Harnas Baharuddin (Manunggal Halim Jaya, 2026)
This research aims to explore the role of technology in enhancing human resource (HR) compliance and workforce management, with a focus on organizational agility and employee development. The study adopts a qualitative approach, employing a comprehensive literature review to synthesize existing research on integrating technological tools, such as artificial intelligence (AI), cloud computing, and data analytics, into HR practices. By analyzing a range of scholarly articles, case studies, and industry reports, the study investigates how technology has reshaped HR compliance processes, improved decision-making, and fostered a more agile, resilient workforce. The research reveals that technological solutions have significantly automated compliance tasks, reduced human error, and enhanced real-time monitoring of labor law compliance. Additionally, integrating AI-driven recruitment tools, employee performance systems, and digital learning platforms has proven effective in improving workforce management and supporting continuous employee development. The findings suggest that organizations adopting technology in HR functions are better equipped to respond swiftly to regulatory changes, optimize workforce productivity, and enhance employee satisfaction. This study highlights the growing importance of technology in achieving sustainable HR practices that contribute to long-term organizational success.